First experiences with adaptive co-management in Para, Brazilian Amazon - Pokorny, B.; Cayres, G.; Nunes, W.; Segebart, D.; Drude, R. (CIFOR and Embrapa Amazonia Oriental, 2002)
Adaptive Co-Management (ACM) is an integrative approach for implementing sustainable forest management. An ACM team started working on ACM in Para State in year 2000. Its pilot activities in Para were carried out in three sites, each representing different realities of communities established in the Eastern Amazon region. The research focused on the concept of Collaborative Diagnostic Studies (CDS) as an opportunity to replace extenally-driven background studies, which are important for documentation and impact monitoring, with a collaborative evaluation of an expert-defined set of criteria and indicators for assessing sustainability (C&I). The defined set of C&I was structured in three categories: collaboration, adaptive management of natural resources and impacts/conditions. A variety of participatory methods were tested, described and evaluated in relation to their contribution to ACM. Pilot studies showed that CDS are not suitable as a substitute for background studies. Special efforts have to be undertaken so as to diminish the danger of external dominance and to ensure the participation of local actors. The pilot studies also confirmed the need for a systematic and well structured documentation of the complex and dynamic processes related to ACM. Due to the promising results obtained so far, it is recommended to focus ACM research in Brazil on work shared with local researcher teams and existing community projects.